Simulation training for improving the quality of care for older people: an independent evaluation of an innovative programme for inter-professional education. Issue 6 (6th December 2012) - Ross, Alastair J; Anderson, Janet E; Kodate, Naonori; Thomas, Libby; Thompson, Kellie; Thomas, Beth; Key, Suzie; Jensen, Heidi; Schiff, Rebekah; Jaye, Peter
Abstract : Introduction: This paper describes the evaluation of a 2-day simulation training programme for staff designed to improve teamwork and inpatient care and compassion in an older persons' unit. Objective: The programme was designed to improve inpatient care for older people by using mixed modality simulation exercises to enhance teamwork and empathetic and compassionate care. Methods: Healthcare professionals took part in: (a) a 1-day human patient simulation course with six scenarios and (b) a 1-day ward-based simulation course involving five 1-h exercises with integrated debriefing. A mixed methods evaluation included observations of the programme, precourse and postcourse confidence rating scales and follow-up interviews with staff at 7–9 weeks post-training. Results: Observations showed enjoyment of the course but some anxiety and apprehension about the simulation environment. Staff self-confidence improved after human patient simulation (t=9; df=56; p<0.001) and ward-based exercises (t=9.3; df=76; p<0.001). Thematic analysis of interview data showed learning in teamwork and patient care. Participants thought that simulation had been beneficial for team practices such as calling for help and verbalising concerns and for improved interaction with patients. Areas to address in future include widening participation across multi-disciplinary teams, enhancing post-training support and exploring further which aspects of the programme enhance compassion and care of older persons. Conclusions: The study demonstrated that simulation is an effective method for encouraging dignified care and compassion for older persons by teaching team skills and empathetic and sensitive communication with patients and relatives.